STUDI PENDAHULUAN: PROBLEMATIKA PEMBELAJARAN FISIKA SMA - WIDIARINI, PUTU; RAPI, NI KETUT; SUASTRA, I WAYAN; SUMA, KETUT (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Education is expected to be able to form a whole person who is aware of the importance of comprehensive learning in facing global challenges so that education must provide opportunities for students to learn in a learning process that is optimally designed. Science learning, especially physics, cannot be separated from identifying natural phenomena through observation activities and deeper exploration through experimental activities. However, there are still many challenges in implementing science learning, especially physics in the field. To identify the problems of science learning, especially high school physics, this study was conducted with the hope of obtaining accurate data related to the problems faced by educators and students. This research is classified as qualitative research with a case study type. The research data will be analyzed through three stages, namely data reduction, data presentation, and drawing conclusions and verification. The subjects in this study were school principals, physics teachers, and high school students in Singaraja city. The focus of the research is focused on six aspects related to problems or challenges in physics learning, namely: aspects of student readiness, teacher readiness, IT-based learning innovation, learning process, learning facilities, and high school student learning outcomes. ABSTRAKPendidikan diharapkan mampu membentuk manusia seutuhnya yang menyadari pentingnya pembelajaran yang komprehensif dalam menghadapi tantangan global sehingga pendidikan harus memberikan kesempatan kepada peserta didik untuk belajar dalam suatu proses pembelajaran yang dirancang secara optimal. Pembelajaran IPA khususnya fisika tidak dapat dipisahkan dari mengidentifikasi fenomena alam melalui kegiatan observasi dan eksplorasi yang lebih dalam melalui kegiatan eksperimen. Akan tetapi, masih banyak tantangan dalam pelaksanaan pembelajaran IPA khususnya fisika di lapangan. Untuk mengidentifikasi permasalahan pembelajaran IPA khususnya fisika SMA, penelitian ini dilakukan dengan harapan dapat memperoleh data yang akurat terkait permasalahan yang dihadapi oleh pendidik dan peserta didik. Penelitian ini tergolong penelitian kualitatif dengan jenis studi kasus. Data penelitian akan dianalisis melalui tiga tahap yaitu reduksi data, penyajian data, serta penarikan simpulan dan verifikasi. Subjek dalam penelitian ini adalah kepala sekolah, guru fisika, dan peserta didik SMA di kota Singaraja. Fokus penelitian difokuskan pada enam aspek terkait permasalahan atau tantangan dalam pembelajaran fisika yaitu: aspek kesiapan peserta didik, kesiapan guru, inovasi pembelajaran berbasis IT, proses pembelajaran, sarana prasarana pembelajaran, dan hasil belajar peserta didik SMA.